The Importance and Necessity of Assessing the Efficiency of the Internal Control System - Nizomov Olim Kosimjonovich (International Journal on Economics, Finance and Sustainable Development, 2022)
This article describes the essence of the internal control system. As a result of the conducted research, proposals were developed to improve the evaluation of the effectiveness of the internal control system.